Pelepasan monomer resin komposit nanofil dan mikrohibrid dengan penyinaran berbeda - Ratnasari, Dina; Elsa Prahasti, Anastasia; Elline (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Many factors affect the elution of composite resin monomers, such as filler size and light-curing unit used. Objectives: to compare the effect of the filler size and light-curing unit on the elution of monomers. Methods: Subjects were 20 composite resins, consists of 10 microhybrid composite resins and 10 nanofilled composite resins, diameter 4.5 mm and height 2 mm. Composite specimens were cured using halogen light-curing unit 680 mW/cm² or LED 1000 mW/cm², for 20 seconds according to group random allocation. Specimens were put into 1 mL artificial saliva, soaked for 24 hours and then were analyzed with LC-MS/MS, for TEGDMA elution. Results: Two-ways ANOVA test showed there were differences in the influence of filler size and light-curing units type on monomer elution (p < 0.05). The mean of monomer TEGDMA eluted from micro-hal 2.4960 µg/mL ± 0.49318 µg/mL, micro-LED 0.03114 µg/mL ± 2.0820 µg/mL, nano-hal 1.8120 µg/mL ± 0.24273 µg/mL, and nano-LED 1.5000 µg/mL ± 0.0255 µg/mL. Tukey test showed microhybrid composite resin eluted more TEGDMA than nanofilled composite resin (p < 0.05). There were no significant differences in the elution of TEGDMA monomers with the use of light-curing unit halogen or LED (p > 0.05). Conclusion: Different filler size influenced the elution of composite resin monomer. The polymerization of the nanofilled composite resin is better than microhybrid composite resin, proved by less nanofilled composite resin monomer eluted. The use of halogen light-curing unit or LED light-curing unit, showed no difference in the effect on the elution of monomer.